A high-resolution projected climate dataset for Vietnam: Construction and preliminary application in assessing future change. Issue 9 (6th August 2022) - Tran-Anh, Quan; Ngo-Duc, Thanh; Espagne, Etienne; Trinh-Tuan, Long
Abstract: This study generates a daily temperature and precipitation dataset over Vietnam at a high resolution of 0.1° for the historical period 1980–2005 and the future period 2006–2100 under four representative concentration pathway (RCP) scenarios, namely RCP2.6, RCP4.5, RCP6.0, and RCP8.5. The bias correction (BC) and spatial disaggregation (SD) method is applied to the outputs of 31 global climate models (GCMs) of the Coupled Model Intercomparison Project Phase 5 (CMIP5) to create the new dataset called CMIP5-VN. To guide the BC and SD steps, gridded temperature and precipitation data interpolated from daily observations of 147 and 481 stations respectively are used. Results with the CMIP5-VN show that warming over Vietnam is projected to continue till the end of the 21st century under all four RCPs. The average temperature is projected to increase by 1.3±0.52 °C under RCP2.6 and by 3.85±0.85 °C under RCP8.5 between 2080–2099 and 1986–2005. The future increase is more intense in the northern regions than in the south and higher in summer than in winter. Precipitation is projected to increase by 1.16±7.1% under RCP2.6 and by 4.41±9.2% under RCP8.5. In Central Vietnam, there is a consistent rainfall increase in the future rainy season. HIGHLIGHTS: This is the first time a complete set of high-resolution temperature and precipitation data for different scenarios has been created for Vietnam. Besides RCP4.5 and RCP8.5, this is the first time the detailed changes under the RCP2.6 and RCP6.0 scenarios in the sub-regions of Vietnam are assessed. The warming is more intense in the northern regions than in the south and higher in summer than winter for all RCPs. Projected temperature changes relative to the baseline period 1986–2005 based on the newly-created CMIP5-VN data for Vietnam. Five-year moving averages are applied. Colored lines show the ensemble means of the models, and colored shaded areas present the uncertainty ranges (±1 standard deviation) for each representative concentration pathway (RCP) scenario. The number of models used for each RCP is shown in brackets. Box plots display the occurrence statistics (the ends of the box are the upper and lower quartiles, the horizontal line inside the box marks the median, and the two horizontal lines outside of the box indicate the 10th and 90th percentile values, respectively) for warming levels at the end of the 21st century. Graphical Abstract